Retinoic acid modulates intrahippocampal levels of corticosterone in middle-aged mice: consequences on hippocampal plasticity and contextual memory - Bonhomme, Damien; Pallet, Véronique; Dominguez, Gaelle; Servant, Laure; Henkous, Nadia; Lafenetre, Pauline; Higueret, Paul; Béracochéa, Daniel; Touyarot, Katia (Frontiers in Aging Neuroscience, 2014)
It is now established that vitamin A and its derivatives, retinoic acid (RA), are required for cognitive functions in adulthood. RA hyposignaling and hyperactivity of glucocorticoid (GC) pathway appear concomitantly during ageing and would contribute to the deterioration of hippocampal synaptic plasticity and functions. Furthermore, recent data have evidenced counteracting effects of retinoids on GC signaling pathway. In the present study, we addressed the following issue: whether the stimulation of RA pathway could modulate intrahippocampal corticosterone (CORT) levels in middle-aged mice and thereby impact on hippocampal plasticity and cognitive functions. We firstly investigated the effects of vitamin A supplementation and RA treatment in middle-aged mice, on contextual serial discrimination task (CSD), a paradigm which allows the detection of early signs of age-related hippocampal-dependent memory dysfunction. We then measured intrahippocampal CORT concentrations by microdialysis before and after a novelty-induced stress. Our results show that both RA treatment and vitamin A supplementation improve “episodic-like” memory in middle-aged mice but RA treatment appears to be more efficient. Moreover, we show that the beneficial effect of RA on memory is associated to an increase in hippocampal PSD-95 expression. In addition, intrahippocampal CORT levels are reduced after novelty-induced stress in RA treated animals. This effect cannot be related to a modulation of hippocampal 11β-HSD1 expression. In addition, RA treatment induces a modulation of retinoic acid receptors RARα and RARβ expression in middle-aged mice, a finding which has been correlated with the amplitude of intrahippocampal CORT levels after novelty-induced stress. Taken together, our results suggest that the preventive action of RA treatment on age-related memory deficits in middle-aged mice could be, at least in part, due to an inhibitory effect of retinoids on glucocorticoid activity.